Age dynamic of physical condition changes in pre-school age girls, schoolgirls and students, living in conditions of Eastern Siberia - V.Y. Lebedinskiy; E.A. Koipysheva; L.D. Rybina; M.D. Kudryavtsev; S.S. Iermakov; A.Yu. Osipov; L.K. Sidorov (Physical Education of Students)
Purpose: to analyze dynamic of physical condition, considering sex (females) and age of the tested, living in region with unfavorable ecology. Material: we studied pre school age girls (n=1580, age 4-7 years). In the research we did not include children with chronic diseases, who were under observation. We tested schoolgirls (n=3211, age 7-17 years) and girl students (n=5827, age 17-21 years, 1-4 years of study. Girl students were divided into five age groups: from 17 to 21 years. All participants lived in conditions of Eastern Siberia (Irkutsk). This region is characterized by unfavorable ecology and climate geographic characteristics. Results: in dynamic of physical condition of pre-school girls, schoolgirls and students we marked out three substantial periods of it characteristics' changes. Age 7-8 years is critical (transition from 1st to 2nd stage). The least values of these characteristics are found in older (after 17-18 years) ages. In students we observed relative stabilization of these indicators. Conclusions: the received results shall be considered in building physical education training process in pre-school educational establishments, secondary comprehensive schools and higher educational establishments.